Interferensi fonologis pada tuturan bahasa Indonesia pemelajar BIPA dengan bahasa pertama bahasa Prancis - Dhamalia Lantika; Hayatul Cholsy (Jurnal Bahasa Indonesia bagi Penutur Asing, 2023)
Interference is the effect of language learners' first language on their production of the language they are learning. It is a phenomenon that cannot be avoided by a second language learner. One of the most frequent interferences is phonological interference, as it happened to BIPA students with French as their first language. The purpose of this research is to show and explain why the phonological interference happens to them. This research is a qualitative research. The data were obtained using the free method of listening to engagement and recording techniques. The data were transcribed phonemically and phonetically, then analyzed in two ways, namely contrastive analysis and comparative descriptive analysis. Based on this research, it was found that BIPA students tend to eliminate the sound [h] which is at the beginning, middle and end of words, pronounce the sound /r/ with [R] uvular, cut syllables in Indonesian words with the syllable system in French, sometimes eliminating sound /s/, pronounce the sound /g/ with [ʒ] inconsistently, and still use the nasal vowel system in their Indonesian. It was also found that the learner's Indonesian speech was better if they spoke another foreign language with a phonological system similar to Indonesian.